Clinical and histological evaluation of the tissue reactions produced by different implants of nylon cable tie in Wistar rats - Santos, Ivan Felismino Charas [UNESP]; Castañeda, Brayan Sayed Lopez [UNESP]; Rodríguez, Nathalia N [UNESP]; Júnior, José Ivaldo de Siqueira Silva [UNESP]; Ferreira, Gustavo Manea [UNESP]; Silva, Bruna Martins [UNESP]; Loibl, Louise Tolffo [UNESP] (Universidade Federal do Paraná, 2019)
The aim of this study was to evaluate clinically and histological the tissue reactions produced by the implantation of the nylon cable tie transparent and colored in Wistar rats. Wistar male Wistar rats, aged 16 weeks, and weight between 350 and 450 grams were used. The rats were allocated in two groups of 24 animals: Group 1 - rats submitted to the implantation of the monofilament surgical nylon suture (Control Group); Group 2 - rats submitted to the implant of fragment of the transparent and colored nylon cable tie (Experimental Group). The implants of the animals of control group were performed with 5 mm of nylon suture monofilamentar between the carnosus and left paravertebral muscle; and 5 mm fragment were implanted in animal of experimental group of the transparent and colored nylon cable tie in the same region on opposite sides and equidistant from the spine. Eight rats from each group underwent euthanasia to perform the excisional biopsy of the implants for posterior histological examination in three moments: seventh day, 15th day and 90th day after implantation. Infection and / or inflammation evaluation was performed every 24 hours. Multifocal circumscribed lesions around the three implants were observed in 46.7% of the rats, between the first and seventh day after implantation. Acute inflammatory reaction was absent in all groups at the moments evaluated. Chronic inflammatory reaction was observed in the suture group and the clamps at all moments of evaluation except on the seventh day after the implantation in the group of transparent nylon cable tie. Mixed inflammatory reaction was observed in the suture group and the clamp bands on the seventh and 15th day. The implants of monofilament surgical nylon suture (Control Group), transparent and colored nylon cable tie (Experimental Group) showed similar macroscopic (clinical) and histological reactions in Wistar rats in a period of 90 days.
Avaliação clínica e histológica das reações teciduais produzidas por diferentes implantes da abraçadeira autoestática de náilon em ratos wistar
Keywords: Cable tie; Histology; Macroscopy; Small animals; Surgery